Cultural Intelligence: A Systematic Review of Library Management and Local Wisdom for SDG 4 - Ahmad Rihal, Henky; sri; Afrina, Cut; Amaliah, Eni (UIN Raden Intan Lampung, 2026)
Current developments in education show that libraries are also places for lifelong learning, thereby significantly supporting the sustainable development goal of Quality Education. In several countries, including Indonesia, variations in access, ethnic diversity of the population and the need for increasingly diverse curricula are encouraging libraries to use management approaches that are sensitive to the cultural complexity of users. on the dimensions of Motivation (CQ Drive), Cognitive (CQ Knowledge), Metacognitive (CQ Strategy), and Behaviour (CQ Action) with library management practices, How cultural intelligence is applied in library operations to support inclusion and quality education in SDG 4, which managerial strategies and collection policies successfully incorporate local knowledge so as to strengthen contextual learning and equitable access, evidence and policies linking SDG 4 indicators to culturally sensitive library service outcomes. The research method used in this study is a systematic literature review. Data sources were obtained from searching articles in research journal databases and searching the internet. The main database used was Google Scholar for the last 10 years, from 2015 to 2025. The results of the study indicate that integrating the framework of Cultural Intelligence and local wisdom into library management has proven to be a strategic and relevant approach, despite being relatively new. This integration has had a positive impact, such as increased participation, access and relevance of library services for diverse communities. Local wisdom plays an important role in strengthening cultural identity and making services more inclusive and empowering. This approach effectively links the function of libraries to SDG 4 (Quality Education), positioning libraries as agents of culture-based empowerment. To support this, an adaptive management model is required, with specific recommendations on the development of contextual cultural intelligence training, the documentation of best practices based on local wisdom, and the formulation of measurable performance indicators related to the SDGs